Book-Tax Differences and Profit Growth: Evidence from Indonesia - Qurrotal Qolbiyah; Muhammad Isa Alamsyahbana; Rachmad Chartady; Armansyah Armansyah; Yerisma Welly (Ilomata International Journal of Tax and Accounting, 2023)
This study aims to examine the effect of permanent and temporary differences as well as book-tax differences on profit growth in property and real estate firms listed on the Indonesia Stock Exchange (IDX). Permanent differences refer to the differences between taxable income and accounting income that cannot be reversed in the future, while temporary differences are the differences that will reverse over time. The study focused on the sub-sector of property and real estate, which was selected because these companies are considered high-risk and often adopt strategies to legally minimize their tax burden in order to maximize profits.. Purposive sampling was used to select a sample of 12 property and real estate firms that consistently published audited financial statements in Indonesian Rupiah from 2018 to 2021 and did not undergo delisting from the IDX during that period. The results of the analysis reveal that profit growth is positively and significantly influenced by both permanent and temporary differences. However, there was no significant impact observed from book-tax differences. These findings may provide insights for policymakers and investors in the property and real estate sector.